Are some more equal than others? Animated and animatronic adaptations of Animal Farm. Issue 10 (3rd October 2021) - Marks, Peter
ABSTRACT: This article focuses on two film adaptations of George Orwell's 1945 novel Animal Farm, exploring what they tell us about the Cultural Cold War and the post-Cold War period, as well as about the interplay between adaptation and political purpose. The article situates the 1945 animated version in the context of the Cultural Cold War, touching on the now well-established CIA involvement of this version, and investigating how that film's ending especially reflects specific propaganda agendas. The less-considered 1999 animatronics version is read in terms of its substantial refocusing of narrative and point-of-view to foreground the situation of refugees and dissidents in the post-Cold War world in which it first appeared. The article argues that this adaptation ignores Orwell's powerful and ambiguous ending in ways that are different from the 1945 version but equally problematic. While accepting that no adaptation is required to observe fidelity to an originary text, the article suggests that both these cinematic takes reconfigure the novel for political ends fundamentally at odds with those in Orwell's Animal Farm .